JLIBRARY AS AN ENGLISH LEANING MEDIA BASED ON ICT ( INFORMATION COMMUNICATION AND TECHNOLOGY) - Ulfa Wulan Agustina (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2020)
ABSTRACT In this era english become one of the foreign language which is studied in Indonesia by almost people..There are many skills which we studied in English such as reading ,speaking,listening and also writing. Reading sometimes become the most bired actitities through students because it was passive activities. According to this reason this paper aims to design English learning media learner as a media that appropriate for their learning needs. JLIBRARY is some technology whuch is developed by using ICT method emphasizes on textual android app. It was done for time efficiency in learning a language. The simple and clearly technique are used in the implementation of JLIBRARY method in learning English. There were two researches objective; these are designing JLIBRARY and knowing the feasibility of the english learning media. The researcher uses Research and Development method adapted from Sadiman’s development. The researcher concludes that JLIBRARY is feasible to use in English Learning Media. KEYWORDS: Jlibrary,English media,ICT ABSTRAK Bahasa Inggris adalah salah satu bahasa asing yang dipelajari di Indonesia saat ini. Sebagai sarana komunikasi, salah satu keterampilan yang paling penting adalah keterampilan berbicara atau percakapan dalam bahasa Inggris. Makalah ini bertujuan untuk merancang media pembelajaran bahasa Inggris untuk pelajar muda sebagai media yang sesuai dengan kebutuhan belajar mereka. Metode JLIBRARY menekankan pada aplikasi android tekstual. Hal ini dilakukan untuk efisiensi waktu dalam mempelajari suatu bahasa. Teknik yang sederhana dan jelas digunakan dalam penerapan metode JLIBRARY dalam belajar bahasa Inggris. Ada dua tujuan penelitian; ini merancang JLIBRARY dan mengetahui kelayakan media pembelajaran bahasa Inggris. Peneliti menggunakan metode Penelitian dan Pengembangan yang diadaptasi dari pengembangan Sadiman. Peneliti menyimpulkan bahwa JLIBRARY layak untuk digunakan dalam Media Pembelajaran Bahasa Inggris. Kata Kunci: Jlibrary,English media,ICT